Effect of the high-level trigger for detecting long-lived particles at LHCb - Calefice, Lukas; Hennequin, Arthur; Henry, Louis; Jashal, Brij; Mendoza, Diego; Oyanguren, Arantza; Sanderswood, Izaac; Sierra, Carlos Vázquez; Zhuo, Jiahui; , Part of LHCb-RTA Collaboration (Frontiers in Big Data, 2022)
Long-lived particles (LLPs) show up in many extensions of the Standard Model, yet are challenging to search for with current detectors, due to their very displaced vertices. This article evaluates the ability of the trigger algorithms used in the LHCb experiment to detect long-lived particles, and work to adapt them in order to enhance the sensitivity of this experiment to undiscovered long-lived particles. A model with a Higgs portal to a dark sector is tested, and the sensitivity reach is discussed. In the LHCb tracking system, the farthest tracking station from the collision point is the Scintillating fiber tracker, the SciFi detector. One of the challenges in the track reconstruction is to deal with the large amount and combinatorics of hits in this detector. A dedicated algorithm has been developed to cope with the large data output. When fully implemented, this algorithm would greatly increase the available statistics for any long-lived particle search in the forward region, and would additionally improve the sensitivity of analyses dealing with Standard Model particles of large lifetime, such as Ks or Lambda hadrons.